1963
DOI: 10.1107/s0365110x63001584
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in irradiated BeO

Abstract: X-ray diffraction studies of polycrystalline beryllium oxide irradiated to 1.5 x 1021 nvt (En > 1 Mev) at 110 °C have shown selective symmetric or asymmetric broadening of reflections Me.1 with 1 not zero. Displacements of reflection maxima and centroids occur in such a manner that a unique a a lattice parameter cannot be defined from spacing measurements. Models of clustered interstitial and vacancy defects in a damaged BeO lattice have been proposed and the X-ray scattering from these models has been calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…First, study of magnetic ordering on the Mn 3+ ions is more straightforward in YMnO 3 than in the rare earth manganites since there is no perturbation from the rare earth f -electron magnetic moment. In addition, YMnO 3 forms both the hexagonal and orthorhombic phases on solution synthesis at ambient pressure [13] making it particularly appealing for use in a comparative study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, study of magnetic ordering on the Mn 3+ ions is more straightforward in YMnO 3 than in the rare earth manganites since there is no perturbation from the rare earth f -electron magnetic moment. In addition, YMnO 3 forms both the hexagonal and orthorhombic phases on solution synthesis at ambient pressure [13] making it particularly appealing for use in a comparative study.…”
Section: Introductionmentioning
confidence: 99%
“…Early (1960s) work on YMnO 3 [13] established the hexagonal phase to be ferroelectric, with the hexagonal perovskite structure and the P 6 3 cm space group. The hexagonal perovskite structure consists of ABCACB... stacking of close packed O layers, with the Mn ions occupying 5-fold coordinated sites, and the rare earth atoms in 7-fold coordinated interstices.…”
Section: Introductionmentioning
confidence: 99%
“…In early works in the 1960s, the ferroelectricity (T C $ 950 K) in hexagonal YMO was ascribed to an offcenter distortion of Mn 3þ towards one of the apical oxygen ions. 79,80 However, recent detailed single crystal x-ray diffraction experiments revealed that the Mn ions remain very close to the centre of the oxygen bipyramids, and the ferroelectric phase should be ascribed to the buckling of the layered MnO 5 bipyramids accompanied by the displacements of the Y ions. 78 The mechanism of the ferroelectricity in hexagonal YMO is associated with the strong hybridization between Y 4d and O 2p states.…”
Section: Antiferromagnetic Rmnomentioning
confidence: 98%
“…I t should be noted that,, whereas the rocking curve scan is tangevstiab in reciprocal space. t'he st'andard scan on conventional diffractomet'ers, such as used by Walker et al [3] and Take1 and Borie [ 5 ] , is a radial scan in reciprocal space. Because of this difference in scanning directjion, it should be expected that apparent line profiles by the two methods would be different, as is the case.…”
Section: Examination Of As-irradiated Rrystalsmentioning
confidence: 99%
“…The appearance of duplex structure in (hkl) reflections was considered by Sabine, who concluded on formal mathematical bases t>hat the duplex structure in X-ray diffraction pat>terns was consistent with the presence of interplanar clust>ers parallel t)o the basal plane [4]. By a somewhat different approach, Yakel and Borie also credited int,erplanar clusters for the observed broadening of ( h k l ) reflect>ions from polycrystalline Be0 [ 5 ) . The presence of small clu-t b ers has also been notjed by neutron scattering [S!…”
Section: Introductionmentioning
confidence: 99%